2017
DOI: 10.1556/0806.44.2016.052
|View full text |Cite
|
Sign up to set email alerts
|

Adult plant resistance of selected Kenyan wheat cultivars to leaf rust and stem rust diseases

Abstract: Phenotypic and genotypic evaluation of wheat genetic resources and development of segregating populations are pre-requisites for identifying rust resistance genes. The objectives of this study were to assess adult plant resistance (APR) of selected wheat genotypes to leaf rust and stem rust and to develop segregating populations for resistance breeding. Eight selected Kenyan cultivars with known resistance to stem rust, together with local checks were evaluated for leaf rust and stem rust resistance at seedlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The FHB severity reaction of genotypes varied across the test environments given the variability in environmental conditions or differences in the aggressiveness of isolates. This was the observed trends across studied experimental sites with alternating wet and warmer environments of South Africa (Goswami and Kistler 2004;Figlan et al 2017). Cedara site had higher temperatures and humidity conditions (Table S1) compared to the Bethlehem site.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The FHB severity reaction of genotypes varied across the test environments given the variability in environmental conditions or differences in the aggressiveness of isolates. This was the observed trends across studied experimental sites with alternating wet and warmer environments of South Africa (Goswami and Kistler 2004;Figlan et al 2017). Cedara site had higher temperatures and humidity conditions (Table S1) compared to the Bethlehem site.…”
Section: Discussionsupporting
confidence: 68%
“…The Cedara site is a hotspot area of various plant diseases in South Africa. A recent study revealed a much higher disease pressure of leaf rust in Cedara, compared to other testing sites across the country (Figlan et al 2017).…”
Section: Field Response Of Rils Parents and Checks For Fhb Resistancementioning
confidence: 89%
“…Therefore, low disease development with high infection response on the tested cultivars in each location presenting evidence that the presence of partial resistance in addition to race specific resistance. In harmony with this Figlan, et al[41] reported of the tested Kenyan cultivar (Paka) carry the APR Sr2 gene with race specific resistance gene which exhibited resistance reaction at seedling stage but high infection response at adult stage.…”
mentioning
confidence: 58%